Blue rhenium tricarbonyl DPPZ complexes – low energy charge-transfer absorption at tissue-penetrating wavelengths. Issue 84 (5th October 2016) - Coogan, M. P.; Platts, J. A.
Abstract : Re and Mn DPPZ amido complexes show absorption bands with potential for light harvesting and photodynamic therapy. Abstract : fac -[Re(CO)3 (dppz)] complexes of amido ligands generated in situ under basic conditions display an intense ( ε = 16460 L mol −1 cm −1 ) absorption band between 500–700 nm which are assigned to an n(amido, RNH–) → π* (dppz) inter-ligand charge transfer band offering an extraordinarily low energy charge separating absorption with potential for imaging and energy application.